Hydrogen-Bonding (Thio)urea Organocatalysts in Organic Synthesis : State of the art and practical methods for acetalization, tetrahydropyranylation, and cooperative epoxide alcoholysis - Kotke, Mike; Justus Liebig University Giessen (My University, 2009)
In synthetic organic chemistry the activation of the electrophile, e.g, in nucleophile-electrophile reactions is the domain of Brønsted-acid and metal(-ion) centered Lewis-acid catalysts. They are highly efficient, but suffer from drawbacks resulting from their covalent substrate binding (e.g., product inhibition, high loading, harsh conditions), heavy metal(-ion) contamination (toxicity, lability, costs, time-consuming purification), and/or acidity (substrate/product decomposition, side reactions).To circumvent these drawbacks heavy metal(-ion)- and acid-free, non-covalent and, however, powerful, cost-efficient, stable, and sustainable catalysts operating under mild, (nearly) neutral conditions are highly desirable, e.g., for applications in pharmaceutical and nutrition chemistry. Hydrogen-bonding (thio)urea organocatalysts, purely organic compounds utilizing non-covalent substrate binding, were suggested to meet these requirements. However, their catalytic potential for organic synthesis had been unutilized.This PhD thesis therefore aims at the development of hydrogen-bonding (thio)urea organocatalysts and their implementation in useful preparative-scale organic syntheses. Experimental, analytical (NMR, IR, GC, GC/MS, HPLC, HRMS) as well as computational approaches were utilized. Six chapters document the research projects and results achieved in course of this PhD thesis:The chapter "(Thio)urea Organocatalysts" based on intensive literature research critically and comprehensively reviews the success story and applications of all hydrogen-bonding mono- and bifunctional (thio)urea organocatalysts in (non-)stereoselective organic synthesis for the period 1984 2008; (184 schemes; 64 figures). It is entirely published as core contribution (204 printed pages, chapter 6) in the Wiley-book "Hydrogen Bonding in Organic Synthesis": "Chapter 6, dedicated to organocatalysis using thioureas, is a real gem! ... The chapter is self-contained and could be easily reprinted as a separate book." (cited from book review: J. Am. Chem. Soc. 2010, 132, 6863)Five practical organocatalytic procedures (1.) (5.) were developed; the resulting three original journal publications are given in chapter 2:(1.) The acetalization of aldehydes and ketones in the presence of orthoester as alcoholate source (14 substrate examples), (2.) the tetrahydropyran (THP) protection (tetrahydropyranylation), and (3.) the 2-methoxypropene (MOP) protection of diverse alcohols, phenols, and other ROH derivatives (more than 40 examples) were found to be catalyzed by the N,N´-bis[3,5-(trifluoromethyl)phenyl]thiourea at very low loadings (0.001 1 mol%). Catalytic efficiency is high with TON values of 100,000 and TOF values of up to 5700/h. These are the most efficient organocatalytic reaction reported to date. A recyclable polystyrene-bound thiourea catalyst was introduced to improve the practicability further as demonstrated in selected THP protections.The (4.) completely regioselective alcoholysis of styrene oxides (18 examples) and (5.) the direct formation of 1,3-dioxolanes from carbonyl compounds and styrene oxides (11 examples) turned out to require a cooperative Brønsted acid-type organocatalytic system; it comprises of the individual components mandelic acid (1 mol %) and N,N´-bis[3,5-(trifluoromethyl)phenyl]thiourea (1 mol %). This "Cooperative organocatalysis" is an innovative and seminal catalysis concept developed herein; various applications appear to be feasible such as "activity tailoring".The procedures (1.) (5.) operate under mild (25 or 50 °C), (nearly) neutral conditions, tolerate a broad substrate scope, e.g., stericallyhindered, acid- and T-sensitive substrates. Excellent yields at high purities (more than 99.5%) and ready work-up even inroutine preparative-scale experiments (up to 200 mmol) underline their synthetic utility. Acyclic, cyclic acetals (1,3-dioxolanes) (from 1. and 5.), THP (2.) and MOP ethers (3.) as well as beta-alkoxy alcohols (4.), all synthetically useful compound classes, for the first time have become organocatalytically accessible.Based on both experiments and high-level computations for each method a detailed mechanistic scenario is visualized as catalytic cycle to interpret product formation and the catalyst s mode of action through explicit double hydrogen bonding; novel activation concepts were identified.Additionally, this PhD thesis presents a straightforward multi-gram preparation of the privileged N,N´-bis[3,5-(trifluoromethyl)phenyl]thiourea catalyst (scale: 100 mmol; yield 36.1 g; 84%) and 3,5-bis(trifluoromethyl)phenyl isothiocyanate (scale: 40 mmol; yield: 8.0 g; 74%).Eight Chiral oxazoline-thiourea derivatives incorporating the 3,5-bis(trifluoromethylphenyl)thiourea moiety were prepared utilizing the experimental protocol elaborated herein. They were envisioned to serve as bifunctional enantioselective hydrogen-bonding catalysts; test reactions revealed this novel thiourea class to be catalytically inactive likely owing to a strong intramolecular hydrogen bond; modified oxazoline-thiourea structures and synthetic routes are suggested and discussed.The crystal structure of N,N´-bis[3,5-(trifluoromethyl)phenyl]thiourea was measured with X-ray diffraction, solved, and refined; it is illustrated with all crystallographic key data, selected bond lengths, and angles. The syn orientation of the NH protons (trans/trans rotamer) crucial for the catalyst s clamp-like double hydrogen-bonding interactions is confirmed.Beyond catalysis: The gram-scale syntheses of 4-(methylthio)butyl isothiocyanate (ITC) (Erucin) and 5-(methylthio)pentyl isothiocyanate (Berteroin) were developed. These four-step, cost-efficient syntheses provided these ITCs in high grade (more than 99.9%) for a series of cancer research studies in human HepG2 cells test systems. The interdisciplinary medical chemistry project demonstrated the ITCs to be "Janus" compounds with ambivalent character both significant genotoxicity and antigenotoxicity.

In der organischen Synthesechemie, z. B. bei den oft genutzten Nucleophil-Elektrophil-Reaktionen, ist die katalytische Aktivierung des Elektrophils meist unerlässlich und entscheidend für den Reaktionserfolg. Hierfür werden bevorzugt Brønsted-Säure- und metall(-ionen)haltige Lewis-Säure-Katalysatoren verwendet. Diese sind zwar katalytisch sehr effektiv, zeigen aber Nachteile, die aus der kovalenten Substrat-Katalysator-Bindung (z. B. Produkt Inhibition, hohe Beladung und T), dem (Schwer)Metall(ionen)-Gehalt (Toxizität, Labilität, Kosten, zeitintensive Reinigung) und/oder dem Säuregehalt (Substrat-/Produktzersetzung, Nebenreaktionen) resultieren. Dies schränkt deren Anwendungsbereich z. B. in der Pharma- oder Lebensmittelindustrie stark ein, so dass dort oft auf teuere Biokatalysatoren (u. a. Enzyme) oder Synzyme zurückgegriffen werden muss.Um diese Nachteile möglichst auszuschließen, sind alternative oder ergänzende Katalysatoren und Katalysekonzepte notwendig; sie sollten möglichst nicht-kovalent, (schwer-)metall(-ionen)- und säurefrei sein. Wasserstoffbrücken-bildende (Thio)Harnstoff-Organokatalysatoren (H-Brücken-Donoren) sind neutrale, elektronenarme (Thio)Harnstoffderivate, rein organisch und aktivieren Substrate (H-Brücken-Akzeptoren) durch nicht-kovalente (H-Brücken) Bindungen (Nicht-kovalente Organokatalyse). Diese bisher vernachlässigte Katalysatorklasse erfüllt die genannten Anforderungen; ihr Potenzial war aber zu Beginn dieser Arbeit kaum erkannt oder synthetisch genutzt:Die vorrangige Zielsetzung dieser Dissertation war folglich die Entwicklung wasserstoffbrücken-bildender (Thio)Harnstoff-Organokatalysatoren und deren praktische Anwendung wie Etablierung für nützliche organische Synthesereaktionen im präparativen Maßstab.Bei der Katalysatorsynthese und - auswahl, Produktcharakterisierung, Struktur- und Mechanismusaufklärung sowie der Methodenentwicklung/-optimierung wurden experimentelle, analytische (NMR, IR, GC, GC/MS, HPLC, HRMS) sowie computergestützte Methoden eingesetzt. Sechs Kapitel dokumentieren detailliert die Forschungsprojekte und Ergebnisse, die im Rahmen dieser Dissertation bearbeitet bzw. erzielt wurden:Das auf intensiver Literaturrecherche basierende Kapitel "(Thio)Harnstoff-Organokatalysatoren" bietet einen kritischen und umfassenden Überblick über die Erfolgsgeschichte und die Anwendungen aller mono- und bifunktionaler wasserstoffbrücken-bildenden (Thio)Harnstoffkatalysatoren in der (nicht-)stereoselektiven organischen Synthese für den Zeitraum 1984 2008; (184 Schemata, 64 Abb.). Es ist vollständig als Hauptkapitel (Kapitel 6) im Wiley-Buch "Wasserstoffbrückenbindung in der Organischen Synthese" publiziert (204 Druckseiten). "Kapitel 6, es ist der Organokatalyse mit Thioharnstoffen gewidmet, ist eine wahre Pracht!... Das Kapitel ist in sich abgeschlossen und könnte ohne Umstände als separates Buch neu herausgegeben werden." (Übersetzt und zitiert a. d. Engl.: J. Am. Chem. Soc. 2010, 132, 6863)Fünf praktische organokatalytische Synthesemethoden (1.) (5.) wurden entwickelt; die drei originalen Journalpublikationen hierzu sind Teil dieser Dissertation (Kapitel 2):(1.) Die Acetalisierung von Aldehyden und Ketonen mit diversen Alkoholen in Gegenwart von Orthoester als Alkoholatquelle (14 Substrat-Bsp.), (2.) die Tetrahydropyran- (THP) (Tetrahydropyranylierung) und (3.) die 2-Methoxypropen- (MOP) Schützung diverser Alkohole, Phenole und anderer ROH-Derivate ( mehr als 40 Bsp.) werden durch den wasserstoffbrücken-bildenden N,N´-Bis[3,5-(trifluormethyl)phenyl]-thioharnstoff (Beladung: 0,001 1 mol%) katalysiert. Mit TON-Werten von 100000 und TOF-Werten bis 5700/h sind dies die bisher wirksamsten Organokatalysereaktionen. Ein polymer-gebundener, einfach filtrativ abtrennbarer, recycelbarer Thioharnstoff-Katalysator wurde eigens zur Steigerung der Praktikabilität der THP-Schützungen entwickelt und erfolgreich präparativ eingesetzt. Für die (4.) vollständig regioselektive Alkoholyse terminaler Styroloxide (18 Bsp.) und (5.) die direkte Synthese von 1,3-Dioxolanen aus Styroloxiden und Carbonylverbindungen (11 Bsp.) wurde ein Brønsted-Säure-artiges Organokatalysesystem bestehend aus den Einzelkomponenten Mandelsäure (1 mol%) und N,N´-Bis[3,5-(trifluormethyl)phenyl]-thioharnstoff (1 mol%) entwickelt. Diese "Kooperative Organokatalyse" ist ein innovatives Konzept, das hier mit der Epoxidalkoholyse eingeführt wurde und vielfältige Anwendungen in Aussicht stellt.Jede dieser optimierten Methoden (1.) (5.) gelingt unter milden (25 oder 50 °C), (nahezu) neutralen Bedingungen, toleriert ein breites Substratspektrum wie z. B. sterisch anspruchsvolle, säure- und T-empfindliche Substrate. Eine einfache Aufarbeitung und ausgezeichnete Ausbeuten hochreiner Produkte (mehr als 99,5%) nach praktischen Reaktionszeiten selbst bei Experimenten im präparativen Maßstab (bis 200 mmol) unterstreichen den synthetischen Nutzen.Unkatalysierte Referenzexperimente unter identischen Bedingungen zeigten hingegen selbst nach Wochen keinen Umsatz.Acyclische und cyclische Acetale (1,3-Dioxolane) (aus 1. und 5.), THP- (aus 2.) und MOP-Ether (aus 3.) sowie beta-Alkoxyalkohole (aus 4.), allesamt synthetisch bedeutende Verbindungsklassen, sind somit dank dieser Methoden erstmals organokatalytisch herstellbar.Der Mechanismus jeder dieser Synthesemethoden wurde mit Experimenten und quantenmechanischen Berechnungen aufgeklärt und detailliert als Katalysezyklus formuliert, um die Wirkung des Katalysators und die Produktbildung zu verstehen; so konnten neue Aktivierungs-/Katalysekonzepte aufgestellt werden.Zusätzlich wird in dieser Arbeit erstmals eine einfach durchzuführende, kostengünstige Synthese im Gramm-Maßstab (100 mmol-Ansatz; Ausbeute 36 g; 84%) für den privilegierten N,N´-Bis[3,5-(trifluormethyl)phenyl]-thioharnstoff und das für die Thioharnstoffsynthese wichtige 3,5-Bis(trifluoromethyl)phenyl-isothiocyanat (40 mmol; Ausbeute: 8,0 g; 74%) präsentiert. Die Kristallstruktur des N,N´-Bis[3,5-(trifluormethyl)phenyl]-Thioharnstoff-Katalysators wurde röntgenkristallographisch vermessen, gelöst, verfeinert und ist mit Angabe aller kristallographischer Schlüsseldaten abgebildet. Die für die doppelte Wasserstoffbrückenbindung erforderliche syn-Orientierung der NH-Protonen (trans/trans-Rotamer) wurde so bestätigt.Chirale Oxazolin-Thioharnstoffderivate wurden als potenziell bifunktionale enantioselektive Katalysatoren eingeführt, eine Synthesestrategie ausgearbeitet und zu einer experimentellen Prozedur optimiert; acht Vertreter dieser neuen Verbindungsklasse wurden hergestellt, vollständig spektroskopisch charakterisiert und in organischen Testreaktionen untersucht. Der erwartete Katalyseeffekt blieb vermutlich aufgrund einer starken intramolekularen H-Brücke aus; modifizierte Oxazolin-Thioharnstoffstrukturen und Syntheserouten werden diskutiert.Beitrag zu einem interdisziplinären Krebsforschungsprojekt (Medizinische Chemie): Für 4-(Methylthio)butyl-isothiocyanat (Erucin) und 5-(Methylthio)pentyl-isothiocyanat (Berteroin), chemopreventive Wirkstoffe, wurde eine Syntheseprozedur für die Darstellung im Gramm-Maßstab ausgearbeitet; diese damit in hoher Reinheit (größer als 99,9%) hergestellten Isothiocyanate erwiesen sich in Studien an humanen HepG2-Zellen als "Janus"-Verbindungen mit einem ambivalenten Charakter: Konzentrationsabhängige Gentoxizität und Antigentoxizität.
Wasserstoffbrücken-bildende (Thio)Harnstoff-Organokatalysatoren in der Organischen Synthese : Stand der Forschung und praktische Methoden zur Acetalisierung, Tetrahydropyranylierung und Kooperativen Epoxidalkoholyse
Keywords: Organokatalyse; (Thio)Harnstoffe; Acetalisierung; Tetrahydropyranylierung; Epoxidalkoholyse; organocatalysis; (thio)ureas; acetalization; tetrahydropyranylation; epoxide-alcoholysis; ddc:540